Religious Beliefs, Indigenous Communities and Environmental Preservation in Western Tamil Nadu, South India. - pitchaivelu, kanagaraj (The Trumpeter, 2009)
The article analyses the innate linkages between the religious beliefs of the indigenous communities and environment in western Tamilnadu in India. The utilitarian conservation practiced by these indigenous communities had promoted judicious balance between consumption needs and conservation imperatives. The protection of field and wild biodiversity of the area is secured through the religious institution of totemism. Their folkstories and religious myths portray the organic linkage between religion and environment. Their traditional management of natural resources is environmentally harmonious and sustainable.